2020
DOI: 10.1016/j.ijsolstr.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of the generalized, finite deformation correspondence model of peridynamics

Abstract: A class of peridynamic material models known as constitutive correspondence models provide a bridge between classical continuum mechanics and peridynamics. These models are useful because they allow well-established local constitutive theories to be used within the nonlocal framework of peridynamics. A recent finite deformation correspondence theory (Foster and Xu, 2018) was developed and reported to improve stability properties of the original correspondence model . This paper presents a stability analysis th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…The bond-associated model, without the higher-order corrections, is denoted as BA-PD, which is equivalent to the linear BA-RK-PD. The following numerical examples are provided for a threefold goal: (1) to test the convergence of the different variants of the correspondence model, (2) to demonstrate the unstable behavior of RK-PD and GMLS-PD and that it can be fixed through the bond-associative modeling approach, and (3) to study the robustness obtained by a combination of the bond-associative approach and higher-order corrections.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond-associated model, without the higher-order corrections, is denoted as BA-PD, which is equivalent to the linear BA-RK-PD. The following numerical examples are provided for a threefold goal: (1) to test the convergence of the different variants of the correspondence model, (2) to demonstrate the unstable behavior of RK-PD and GMLS-PD and that it can be fixed through the bond-associative modeling approach, and (3) to study the robustness obtained by a combination of the bond-associative approach and higher-order corrections.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Despite offering convenience in utilizing classical constitutive relations, PD correspondence materials have been found problematic in practice as they involve instability issues. The unstable behavior appears as zero-energy mode oscillations in meshless peridynamic simulations and has been largely attributed to the cancellation of the non-uniform parts of deformation, which is allowed within the integration (averaging) technique [2,7,13,31,36]. The instabilities can lead to large errors in practical applications [16].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these algorithms can compute non-local gradients with n th -order accuracy. We showed that the higher-order corrections cannot eliminate the wellknown issue of numerical instability in correspondence PD theory, which manifest itself as zero-energy mode oscillations in simulations that involve inhomogeneous deformations [3,8,17,24,27], and may lead to large prediction errors in practical applications [16]. To provide stability for the higher-order framework, we developed a continuum-based, bondassociated model, inspired by [4,9,10], which takes into account non-uniform deformations and maintains stability without additional stabilization mechanisms employed.…”
Section: Introductionmentioning
confidence: 93%
“…Peridynamics was introduced as a nonlocal form of continuum mechanics by Silling in 2000 [15] for modeling fracture. Since then, it has been extended to a variety of other problems in which domain changes/discontinuities are part of the problem [5,6,8,[25][26][27][28][29][30][31][32][33][34][35]. In this theory, each material point is connected through peridynamic bonds to other points within a certain neighborhood region called "the horizon".…”
Section: Brief Review Of Peridynamicsmentioning
confidence: 99%